The health equity network of the Americas: inclusion, commitment, and action - Castro, Arachu (2021)
The Health Equity Network of the Americas (HENA) is a multidisciplinary network that promotes knowledge sharing and intersectoral action for equity in health and human rights in the Americas. The objectives of HENA are: 1) to share successful experiences in the development of interventions, considering the social determinants and determination of health, to achieve participatory and community-based health responses; 2) to analyze the health, social, political, environmental and economic impacts of the COVID-19 pandemic; 3) to identify the effects of pandemic care on populations most at risk because of their age and pre-existing health conditions; 4) examine the situation at borders and population movements in the spread of the pan-demic and its effects on migrant populations; 5) propose strategies to ensure access to comprehensive care for pregnant women in order to reduce maternal and neonatal suffering, morbidity, and mortality; and 6) ana-lyze violations of human rights and the right to health of historically marginalized populations, including street dwellers and other communities that depend on public spaces and the street for survival. The analytical and intervention models for health equity at HENA are based on various approaches, including social medicine, social epidemiology, medical anthropology, human ecology, and One Health.